Isotope Substitution Extends the Lifetime of Organic Molecules in Transmission Electron Microscopy. Issue 5 (10th September 2014) - Chamberlain, Thomas W.; Biskupek, Johannes; Skowron, Stephen T.; Bayliss, Peter A.; Bichoutskaia, Elena; Kaiser, Ute; Khlobystov, Andrei N.
<x xml:space="preserve">Abstract</x> Structural characterisation of individual molecules by high‐resolution transmission electron microscopy (HRTEM) is fundamentally limited by the element and electron energy‐specific interactions of the material with the high energy electron beam. Here, the key mechanisms controlling the interactions between the e‐beam and C–H bonds, present in all organic molecules, are examined, and the low atomic weight of hydrogen—resulting in its facile atomic displacement by the e‐beam—is identified as the principal cause of the instability of individual organic molecules. It is demonstrated theoretically and proven experimentally that exchanging all hydrogen atoms within molecules with the deuterium isotope, and therefore doubling the atomic weight of the lightest atoms in the structure, leads to a more than two‐fold increase in the stability of organic molecules in the e‐beam. Substitution of H for D significantly reduces the amount of kinetic energy transferred from the e‐beam to the atom (main factor contributing to stability) and also increases the barrier for bond dissociation, primarily due to the changes in the zero‐point energy of the C–D vibration (minor factor). The extended lifetime of coronene‐d12, used as a model molecule, enables more precise analysis of the inter‐molecular spacing and more accurate measurement of the molecular orientations.